Effects of foliar extracts of guaba (Inga edulis) and cadaghi (Corymbia torrelliana) on coffee (Coffea arabica ‘Caturra Roja’) under nursery conditions in Chanchamayo, Peru - Ojeda, W. (2019)
The objective of this study was to determine the allelopathic effects of leaf extracts of the forest species guaba (Inga edulis) and cadaghi (Corymbia torrelliana) on coffee (Coffea arabica ‘Caturra Roja’) plants grown under nursery conditions in Chanchamayo, Peru. Different doses of fresh leaf extracts were applied to coffee plants using a completely randomized design, with four treatments for each forest species (T1 = 0‰, T2 = 10‰, T3 = 20‰, and T4 = 30‰) and 12 replicate plants per treatment. It was found that none of the foliar extracts had an allelopathic effect on coffee plants in terms of height, stem diameter, number of leaves and dry weight; however fresh weight was significantly altered following “cadaghi” treatment.